Effect of growth regulators on the in vitro propagation and ex vitro root formation of Gnetum gnemon var. griffithii Markgr - Nguyen, Hoang Thi Phuong; Nguyen, Phan Xuan; Hang, Nguyen Thi Thanh; Khiem, Dinh Van (Academia Journal of Biology, 2018)
This study is to investigate the in vitro propagation and ex vitro root formation of Gnetum gnemon var. griffithii Markgr (G. gnemon), one of the nutrient-rich forest vegetables. The results showed that MS medium supplemented with 1.5 mg l-1 BAP was the most suitable combination for shoot formation after 90 days of culture. The combination between 1 mg l-1 BAP and 0.5 mg l-1 NAA gave the best in vitro rooting rate (40%) after 60 days culture. After 60 days tranfered to the greenhouse, plantlets which planted on the substrate of coconut fiber powder had a better growth (plant height of 6.14 cm, root length of 6.90 cm) than those on a combination substrate of coconut fiber powder and sand (1:1). In additional, plantlets treated with 3.0 mg l-1 IBA for 1 minute had the highest root formation rate (80%), the greatest root number per plantlet (2.80 roots), and the longest root (1.76 cm) when compared with those in different of treatment.Nodal segments, PGRs, root formation, shoot formation.